E-demokracija v drugačni demokraciji - Lukšič, Andrej (Teorija in praksa, 2014)
In this article, the author deals with the issue of e-democracy, but neither as a problem sui generis nor in reference to the existing institutional arrangements of the political sphere. The article deviates from the well-established approaches in the scientific and professional literature in the assumption that it is necessary to reconsider the existing institutional arrangements, which have already met with public criticism, if we want to exploit all the potential of information and communication technologies in the political sphere. The author therefore raises the possibility of a new democratic order, which is based on the principle of autonomy, which introduces an understanding of democracy as a bilateral process and which manifests itself in institutionalized opening of political arenas. He then points to the possibility of its virtualization and the possibility of a fuller use of the already developed tools of e-democracy. This new institutional network will create conditions which will encourage and guide further development of new emancipatory ICT tools. These conditions will be established on the basis of the balance of political power and the responses of key civil and political actors to unresolved issues, which are discussed in the second part of the article.
Keywords: Communication technology; e-demokracija; Electronic democracy; Elektronska demokracija; Informacijska tehnologija; informacijsko-komunikacijska tehnologija; information and communications technology; Information technology; Komunikacijska tehnologija; Parlamentarna demokracija; Parliamentary democracy